Implementation Of Mudharaba Agreement In PT. Bank Tabungan Negara (BTN) Tbk. Sharia Business Unit (SBU) Branch Of Semarang - Fiana Zahroh Suciani; Bonar Setyantono; Aryani Witasari (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
This study aims to conduct a study that jurisdiction over on mudharabah at. Bank Tabungan Negara (BTN) Tbk. SBU Branch of Semarang and to know mudharabah implementation constraints on PT. Bank BTN Tbk. SBU Branch of Semarang and how to overcome them. The research method used is normative, the source of the data used are secondary data gathered through identification and inventory of legislation and library books interviews as supporting data, then the data is analyzed by qualitative normative method.Based on the results of research and discussion we concluded that the Agreement Mudharabah is a partnership contract by PT. Bank Tabungan Negara (BTN) Tbk. Sharia Business Unit (SBU) Branch of Semarang to customers of PT. Bank Tabungan Negara (BTN) Tbk. Sharia Business Unit (SBU) Branch of Semarang as shahibul maal finance, hundred percent of funds to the client (mudharib). Implementation mudharabah in PT. Bank Tabungan Negara (BTN) Tbk. Sharia Business Unit (SBU) the new branch also complies with Islamic legal theory and the theory of legal certainty.Keywords: Mudharabah; Islamic Banking.